Farmers’ Perception Regarding Custom Hiring Services in Jabalpur District of Madhya Pradesh (Indian Journal of Extension Education, 2022)
Indian agriculture has witnessed a labour crisis and a dearth of farm mechanization resulting in inadequate production and productivity in various parts of the country. The study was undertaken in Jabalpur district of Madhya Pradesh in 2020, to analyse farmers’ perception of Custom Hiring Services (CHS). Patan block was selected purposively by involving 80 respondents spread over ten villages using proportionate random sampling technique. Farmers actively engaged in agricultural operations and availing the services of the Custom Hiring Centres (CHCs) were selected purposively. The majority (75%) of the farmers had moderate perception towards CHS. The independent variables such as age, annual income, cropping pattern, information processing behavior, information sharing behavior and extent of utilization of CHS were found to be significant and positively related with the perception of farmers regarding CHS. Proper measures must be taken for the provision of enhancing mainly small and marginal farmers’ understanding of mechanization as well as ensuring quality and timely services by the CHCs in order to realize its sustainable adoption.